PENDEKATAN ‘PERSON-CENTERED THERAPY’ DALAM KONSELING PASTORAL UNTUK PENGHIBURAN DAN PENGUATAN ROHANI PASIEN KANKER - Sitompul, Hesti (PT. Giat Konseling Nusantara, 2025)
Cancer patients often experience emotional and spiritual distress that affects their quality of life. This study aims to analyze the application of Person-Centered Therapy (PCT) in pastoral counseling to provide spiritual comfort and strengthening for cancer patients. The theoretical study was conducted based on a qualitative approach with a library research method. PCT, developed by Carl Rogers, emphasizes empathy, unconditional acceptance, and active presence, making it relevant to the context of pastoral counseling. The results of the study indicate that the application of PCT can help cancer patients find the meaning of life, increase inner peace, and strengthen their spiritual relationship with God. This study concludes that PCT makes a significant contribution to pastoral care, especially for patients with complex emotional and spiritual needs.